A Synthesis of the Ecology, Human-Related Threats and Conservation Perspectives for the Endangered Franciscana Dolphin - Secchi, Eduardo R.; Cremer, M. J.; Danilewicz, D.; Lailson-Brito, J. (Frontiers in Marine Science, 2021)
The franciscana is endemic to subtropical coastal waters of Brazil, Uruguay, and Argentina, and is the only living species of the family Pontoporiidae. It is regarded as the most endangered cetacean in the western South Atlantic. Five management units are recognized (Franciscana Management Areas, FMAs – sensu Secchi et al., 2003a), with abundance estimates ranging from a few hundred to around 15,000 dolphins. Low reproductive potential and short life span make this species highly susceptible to current non-natural removal rates. Bycatch in gillnet fisheries occurs in high levels since the 1960s in Uruguay and 1980s in Brazil and Argentina. Although other threats exist, such as habitat degradation that includes physical (noise) and chemical pollution, depletion of fish stocks and climate change, incidental mortality in gillnets is currently the greatest threat to franciscanas. Fishing-related mortality ranges from approximately 100, in FMA I, to more than 1,000 in FMA III, and exceed from near two (in FMA IV) to more than five times (in FMA III) the maximum allowed sustainable mortality rate, based on potential biological removal (PBR) approach. These numbers indicate that the species is unlikely to cope with the current levels of bycatch and that urgent and extreme reduction on fishing practice and effort are required to avoid collapse of the franciscana and to lower its risk of extinction. Current mortality levels and projected declines resulted in the listing of the franciscana as “Vulnerable” in the IUCN Red List. Recent fisheries regulations were implemented in areas with extensive bycatch in Brazil and were expected to improve the species’ conservation status. There is evidence, however, that this regulation is insufficient to reduce fishing-related mortality to sustainable levels due to either or both lack of compliance and inadequate regulation strategies. Here we provide a comprehensive review on the franciscana ecology and threats and discuss perspectives for its conservation.